Tooth extrinsic stain remover by Averrhoa bilimbi L extract solution - Listari, Khusnul Munika; Rudhanton, Rudhanton; Nugraeni, Yuli; Salsabila, Syafira (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background : Dental stains are pigmented deposits that can be a predisposing factor for periodontal disease and caused aesthetic problems. Chromogens from foods and beverages such as coffee can adhere to the tooth surface trough pellicle and forming deposits called tooth extrinsic stains. Averrhoa bilimbi L contains oxalic acid which has potential ability to remove it trough oxidation mechanisms. The aim of this study was to investigate the effectiveness of Averrhoa bilimbi L extract solution on extrinsic tooth stain removal.Method : Tooth extrinsic stain models obtained by soaking the teeth in robusta coffee solution. Twenty-four post extraction premolar teeth with extrinsic stains were divided into 4 groups consisting of control group (immersion in artificial saliva), T1 group(immersion in Averrhoa bilimbi L extract solution 50%), T2 group (immersion in Averrhoa bilimbi L extract solution 75%) and T3 group (immersion in Averrhoa bilimbi L extract solution 100%) for 28 hours. Adobe Photoshop CC 2018 used to evaluate the difference color intensity (ΔE) in CieLAB system before and after the treatment.Result : Anova test showed there’s a significant difference within groups (p<0.05). Post Hoc Posttest showed there are significant difference of difference color intensity (ΔE) between each group(p<0.05), with the highest average of it on T3 group then followed by T2 group , T1 group and control. Pearson correlation analysis showed there is a positive correlation between concentration and color intensity.Conclusion : Averrhoa bilimbi L. extract solution proven effective as extrinsic stain removal in vitro.